Strengthening the Value of Moderation as a Solution to Resolving Religious Conflicts that Occur in Indonesia - Qoffal, Sholahuddin; Firmansyah, Ryan; Maimun, Maimun (Seutia Hukamaa Cendekia, 2024)
This article examines the facts of the conflict and the resolution found in resolving the conflict according to the Government of Indonesia, Presidential Regulation of the Republic of Indonesia Number 58 of 2023 concerning Strengthening Religious Moderation. This article aims to be able to implement moderation by the concept of moderation in order to resolve the facts of conflict. This research uses a library study method, namely collecting data from trusted sources such as books, academic journals, articles and relevant documents. The results of the research show that religious conflicts that occur in Indonesia tend to be caused by inappropriate application of moderation, so a solution by strengthening the value of moderation will be very helpful in resolving these conflicts, as are the characteristics of moderation, namely tawassuth, tawazun, I'tidal, tasamuh, mosawa, syura, and ishlah. It is important to apply these seven principles correctly according to the concepts that have been explained.